IDENTIFIKASI TINGKAH ALPHA MALE MONYET HITAM (Macaca nigra) DI CAGAR ALAM TANGKOKO - Mondoringin, Ryan G.H.; Wungow, Rita S.H; Paath, Jantje; Rompas, Joice J.I (Universitas Sam Ratulangi, 2016)
IDENTIFICATION OF ALPHA MALE BLACK MONKEY (Macaca nigra) BEHAVIOR IN THE NATURE RESERVE TANGKOKO. This study aims to get the latest specific data regarding behavior Alpha male / Rambo dominant male in the group 1 in the nature reserve Tangkoko. Materials used 1 Monkey Black Male Dominant (Alpha Male) in group 1 residing Rambo in Tangkoko Nature Reserve Batuangus Bitung, North Sulawesi. The data obtained are analyzed and presented descriptively in the form of graphs or histograms. Based on the results and discussion, it can be concluded as follows: (1) The most long-standing activity Alpha Male / Male Dominance in the morning is locomotion and foraging and agonistic. During the day are: foraging, locomotion, grooming, and inactive. (2) Activities are at least done either in the morning or during the day is the mating activity (coitus). (3) Behaviour Males Dominant Alpha Male is different from other black monkeys in one group Â Keywords: Alpha Male (Macaca nigra), identification of behavior